Application of sequential expanded granular sludge bed reactors for biodegradation of acetate, benzoate, terephtalate and p-toluate in purified terephtalic acid production wastewater. Issue 9 (2nd May 2016) - Lee, Y.S.; Han, G.B.
ABSTRACT: The anaerobic degradation of four major constituents from purified terephtalic acid production wastewater in sequential two expanded granular sludge bed (EGSB) reactors was studied. The performance of the system was evaluated in terms of chemical oxygen demand (COD) removal efficiencies, methane production, stability, granular sludge adaptability as well as reversion of bacterial inhibition. With volumetric loading rates of 1.9–25 kg-COD m −3  d −1 and terephtalate and p -toluate of 584–821 mg L −1, average removal efficiencies of 97.6% and 75.2% were achieved in the EGSB reactors, respectively. In these conditions, gas production reached a total methane production rate of 0.33 L g-COD −1 in the two-stage EGSB reactor system. The disturbance of the EGSB reactors was observed at a feed concentration above around 6.9 g-COD L −1 because of higher influent COD concentration compared to other experiments.